2016
DOI: 10.1016/j.ijgo.2016.06.026
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Intralipid supplementation in women with recurrent spontaneous abortion and elevated levels of natural killer cells

Abstract: Intralipid supplementation did not increase frequency of chemical pregnancy. However, findings related to ongoing pregnancy and live birth should be investigated further. ClinicalTrials.gov:NCT01788540.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 21 publications
1
75
0
Order By: Relevance
“…For the 85 remaining articles, the full texts were examined carefully on the bases of both inclusion and exclusion criteria, and 36 studies were excluded due to unavailable data, lack of intervention group, or small sample size. Finally, results from 49 literatures were selected for further analysis . The process is displayed in a flowchart in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…For the 85 remaining articles, the full texts were examined carefully on the bases of both inclusion and exclusion criteria, and 36 studies were excluded due to unavailable data, lack of intervention group, or small sample size. Finally, results from 49 literatures were selected for further analysis . The process is displayed in a flowchart in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…NK cells can simultaneously mediate cellular and humoral immunity. In addition to high expression on the surface of fetal trophoblast cells, HLA-Cw is also expressed on the surface of T and B cells (16). In conclusion, CD4 + CD25 + Treg and KIR-2DL1 may serve as new targets for the early intervention of URSA.…”
Section: Discussionmentioning
confidence: 99%
“…Many have recommended the need for larger randomized controlled trials to prove the efficacy of intralipid before it can be recommended for routine use. In 2016, Dakhly et al demonstrated that Intralipid administration did not increase the frequency of chemical pregnancy (15). However, they recommended that findings related to ongoing pregnancy and live birth should be investigated further (15).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Dakhly et al demonstrated that Intralipid administration did not increase the frequency of chemical pregnancy (15). However, they recommended that findings related to ongoing pregnancy and live birth should be investigated further (15). They also defined the use of intralipid as a valuable therapy and advised that its use should be based solely on randomized controlled trial (16).…”
Section: Discussionmentioning
confidence: 99%